Adverse plasma fatty acid composition in patients with femoral neck fracture1 - Arsic, Aleksandra; Pesic, Goran; Petrovic, Snjezana; Matic, Aleksandar; Jeremic, Jovana; Jakovljevic, Vladimir; Vucic, Vesna (Canadian journal of physiology and pharmacology, 2020)
Our study aimed to examine the status of plasma fatty acids (FAs), inflammatory markers, and lipid peroxidation in patients with femoral neck fractures. The study included 20 patients (64–86 years) with femoral neck fractures indicated for surgery and a control group of 17 elderly subjects without fractures or serious chronic diseases. Plasma was obtained during the first 12 h postfracture and presurgery and 7 days postop. Compared to the control, patients had significantly higher saturated FA (SFA) and monounsaturated FA as well as increased TNF-α and IL-6. Opposite to that, levels of individual and total n-6 polyunsaturated FA (PUFA), individual and total n-3 PUFA, n-6/n-3 ratio, and levels of thiobarbituric acid reactive substances (TBARS) were markedly lower in the patient than in the controls. On the seventh day after the surgery, we showed a further rise in the SFA, oleic acid, and TNF-α and reductions of n-6 PUFA and IL-6. Taken together, our results suggest that altered FA status, especially reduced PUFA, may influence hip fracture repair and even contribute to femoral fracture susceptibility in the elderly. A potential benefit from nutritional intervention with PUFA in prevention and (or) fracture healing should be considered.